Selection, Characterization, and Application of ssDNA Aptamer against Furaneol - Komarova, Natalia (Molecules, 2018)
Furaneol is an aroma compound which occurs naturally in foods and is used as an artificial flavor. Detection of furaneol is required in food science and food processing industry. Capture- Systematic Evolution of Ligands by EXponential enrichment (SELEX) protocol was applied for the isolation of an aptamer binding to furaneol, a small volatile organic substance contributing to the flavor of various products. Thirteen cycles of selection were performed. The resulting DNA pool was cloned, using blunt-end cloning, and ninety-six plasmids were sequenced and analyzed. Eight oligonucleotides were selected as aptamer candidates and screened for the ability to bind to furaneol, using three different methods—magnetic-beads associated elution assay, SYBR Green I assay, and exonuclease protection assay. One of the candidates was further characterized as an aptamer. The apparent equilibrium constant was determined to be (1.1 ± 0.4) µM, by the fluorescent method. The reported aptamer was applied for development of the ion-sensitive field-effect transistor (ISFET)-based biosensor, for the analysis of furaneol, in the concentration range of 0.1–10 µM.